Developmental Comparison of Ceramide in Wild-Type and Cln3Δex7/8 Mouse Brains and Sera - El-Sitt, Sally; Soueid, Jihane; Al Ali, Jamal; Makoukji, Joelle; Makhoul, Nadine J.; Harati, Hayat; Boustany, Rose-Mary (Frontiers in Neurology, 2019)
CLN3 disease is a neurodevelopmental disease leading to early visual failure, motor decline, and death. CLN3 pathogenesis has been linked to dysregulation of ceramide, a key intracellular messenger impacting various biological functions. Ceramide is upregulated in brains of CLN3 patients and activates apoptosis. Ceramide levels over the lifespan of WT and Cln3Δex7/8 mice were measured using the DGK assay. Ceramide subspecies were determined by LC-MS. Ceramide synthesis enzymes and pre- and post-synaptic protein mRNA expression was measured in Cln3Δex7/8 and normal mouse brains. Neuronal cell death was established by PARP cleavage and Caspases 3/6/9 and cytochrome C mRNA expression in Cln3Δex7/8 and normal mouse brains. In WT mouse, a ceramide peak was noted at 3-weeks of age. The absence of this peak in Cln3Δex7/8 mice might be related to early disease pathogenesis. Increase of ceramide in Cln3Δex7/8 mouse brain at 24-weeks of age precedes neuronal apoptosis. The correlation between serum and brain ceramide in WT mice, and dysregulation of ceramide in serum and brain of Cln3Δex7/8 mice, and the significant increase in ceramide in CLN3 patient and Cln3Δex7/8 mouse brains and sera argue for use of easily accessible serum ceramide levels to track response to novel therapies in human CLN3 disease.